"I need someone who can convince me that life is worth living": Experiences from existential groups led by healthcare chaplains in Norwegian mental healthcare (Nordic Journal of Practical Theology, 2019)
This article explores patients’ experiences of participating in existential groups led by Norwegian healthcare chaplains within mental health specialist services. A qualitative analysis based on the patients’ (N = 157) answers to two open-ended responses in a questionnaire was undertaken. This showed that most of the patients evaluated the groups positively, stating that participating in the existential groups allowed them to increase their self-reflection, let out their feelings, learn new skills, strengthen their self-confidence, and reduce their loneliness. Further, the groups were described as providing spiritual/religious growth and enhanced existential reflection. These results are discussed in relation to a pluralist context and the importance of existential meaning-making formental health.